2021
DOI: 10.3390/microorganisms9020214
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ESβL, AmpC and Colistin-Resistant E. coli in Meat: A Comparison between Pork and Wild Boar

Abstract: A global increase in Escherichia coli (E. coli) resistant to cephalosporins (extended-spectrum β-lactamases (ESβLs) and AmpC β-lactamases) has been recorded in the last 20 years. Similarly, several studies have reported the spread of colistin resistance in Enterobacteriaceae isolated from food and the environment. The aim of the present study was to evaluate the prevalence of ESβL, AmpC and colistin-resistant E. coli isolated from pork and wild boar meat products in the Emilia Romagna region (North Italy). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
1
10
1
Order By: Relevance
“…This result proved that application of phenotypical methods often limited to several antimicrobials, or identification of selected resistance determinants, may lead to underestimation of real AMR status. Similar conclusions were also presented in another study (Rega et al, 2021). That was perfectly illustrated by the E. coli recognized as wild type, isolated from a marsh harrier sampled in nature.…”
Section: Selected Resistance Mechanisms and Potential Transfersupporting
confidence: 84%
“…This result proved that application of phenotypical methods often limited to several antimicrobials, or identification of selected resistance determinants, may lead to underestimation of real AMR status. Similar conclusions were also presented in another study (Rega et al, 2021). That was perfectly illustrated by the E. coli recognized as wild type, isolated from a marsh harrier sampled in nature.…”
Section: Selected Resistance Mechanisms and Potential Transfersupporting
confidence: 84%
“…The phenotypic colistin resistance and related mcr genes were reported in wild mammals including fallow deer in Europe [ 17 ], Barbary macaques in Africa [ 13 ] and Père David’s deer in Asia [ 14 ]. In Italy, phenotypic resistance to colistin without evidence of resistance genes was reported in isolates from hunted wild boars in Emilia Romagna [ 18 ], while phenotypic resistance along with mcr-1 and mcr-2 genes were recently detected in hunted wild boars in Tuscany [ 16 ]. In this study, the phenotypic resistance to colistin was reported in isolates from sympatric domestic and wild ungulates, while in the group of non-sympatric animals it was only detected in livestock.…”
Section: Discussionmentioning
confidence: 99%
“…The blaTEM gene was reported in resistant E. coli from wild boars in Portugal, Poland, and Spain and it was considered by some authors the most frequent gene conferring resistance to β-lactams [ 43 , 45 , 46 ]. Otherwise, in Italy, a low prevalence of bla TEM was reported in resistant isolates from wild boars collected in Emilia Romagna and Lombardy regions [ 18 , 44 ]. Previously, the bla CMY-1 was mainly detected in avian wildlife [ 42 ] and with a low prevalence in resistant E. coli from wild boars in Spain [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations